CD10 expression in urothelial carcinoma of the bladder - Bozkurt Erol R; Bektas Sibel; Behzatoglu Kemal; Bahadir Burak; Ozdamar Sukru O (BMC, 2009)
Abstract Background CD10 antigen is a 100-kDa-cell surface zinc metalloendopeptidase and it is expressed in a variety of normal and neoplastic lymphoid and nonlymphoid tissues. The aim of this study was to evaluate CD10 expression in urothelial carcinoma of the urinary bladder and to determine the correlation between immunohistochemical (IHC) CD10 expression and histopathologic parameters including grade and stage. Methods 371 cases of urothelial bladder carcinomas, all from transurethral resections, were included in this study. Hematoxylin-eosin (HE) stained sections from each case were reevaluated histopathologically according to WHO 2004 grading system. The TNM system was used for pathologic staging. Selected slides were also studied by IHC and a semiquantitative scoring for CD10 expression based on the percentage of positive cells was performed. Results 157 cases (42.3%) showed immunostaining while 214 cases (57.7%) were negative for CD10. 1+ staining was seen in 65 CD10 positive cases (41.4%), and 2+ in 92 cases (58.6%). Overall CD10 expression as well as 2+ immunostaining was significantly correlated with high histologic grade. Overall CD10 expression was also significantly higher in invasive pT1 and pT2-3 tumors compared to noninvasive pTa tumors. pT1 and pT2-3 tumors were also significantly correlated with 2+ immunostaining. Conclusion To date, only a few comparative IHC studies have assessed CD10 expression in urothelial carcinoma of the urinary bladder and this study represents the largest series. Our findings indicate that CD10 expression is strongly correlated with high tumor grade and stage in urothelial carcinoma of the bladder, and that CD10 may be associated with tumor progression in bladder cancer pathogenesis.